PR technologies and tools in the activities of the Ukrainian Rugby Federation during the period of Russia’s large-scale aggression against Ukraine - Pryimak , M.; Kalita , L.; Ivanov , O. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The last decade demonstrates the increasingly active use of new approaches, communication technologies and tools in sports management. Today, every Ukrainian federation to one degree or another uses communication technology, the effectiveness of which has been proven by time – “public relations”. The article examines the peculiarities of the use of PR in the activities of the Ukrainian Rugby (UR) during russia’s large-scale aggression against our country. Objective of the study. Identify and carry out an analysis of the peculiarities of the use of public relations in the activities of the Ukrainian Rugby during the large-scale aggression of russia against our country. Methods. Analysis of documents, monitoring of mass media and Internet resources, sociological survey (questionnaires and interviews), comparison, analysis and synthesis, methods of mathematical statistics. The organization of the study included an analysis of specialized literature, the internal document flow of the UR, monitoring of traditional and electronic mass media, conducting a sociological survey (questionnaire) among UR employees and an interview with the general secretary of the federation I. Arkhytska. The results. Our research made it possible to outline the circle of PR tools actively used by the federation, to carry out their analysis, and also to establish that the PR activities of the UR during the war changed radically. On the recommendation of Rugby Europe, the center of PR - activity was transferred to social networks - Instagram, Twitter (X), Facebook, the YouTube channel of the federation was launched, which contributed to intensifying the impact on the target audience, establishing effective feedback, increasing its reach and opportunities to promote Ukrainian content abroad. Conclusions. PR is a unique phenomenon that informs and at the same time influences public opinion. Thanks to it, a person or organization gets the opportunity to manage relations and form mechanisms of two-way communication. An example of the use of such a well-thought-out and balanced approach in wartime was the UR, which significantly updated its PR toolkit due to the use of innovative technologies.